2014
DOI: 10.1021/ef502204v
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Particle Models with Realistic Morphology and Resolved Microstructure for Simulations of Intraparticle Transport Phenomena

Abstract: Biomass exhibits a complex microstructure of directional pores that impact how heat and mass are transferred within biomass particles during conversion processes. However, models of biomass particles used in simulations of conversion processes typically employ oversimplified geometries such as spheres and cylinders and neglect intraparticle microstructure. Here we develop 3D models of biomass particles with size, morphology, and microstructure based on parameters obtained from quantitative image analysis. We o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 36 publications
5
89
1
Order By: Relevance
“…[123] Data for biomass and its main model compounds changing during pyrolysis are still being studied in the academic community. [124][125][126] To better understand the regime of pyrolysis utilized in experiments, time scale analysis is used. First, the Biot number (Bi) >0.1 indicates that the particle tends to form temperature gradients within it, this case should be avoided.…”
Section: Heat Transfer Limitationsmentioning
confidence: 99%
“…[123] Data for biomass and its main model compounds changing during pyrolysis are still being studied in the academic community. [124][125][126] To better understand the regime of pyrolysis utilized in experiments, time scale analysis is used. First, the Biot number (Bi) >0.1 indicates that the particle tends to form temperature gradients within it, this case should be avoided.…”
Section: Heat Transfer Limitationsmentioning
confidence: 99%
“…4 provides one example of a large particle in which temperature was measured in situ. Though spherical particles are not representative of industrially-relevant biomass feed-stocks, 93 the thermal pathway is still characteristic of wood. Here it can be seen that endothermic phenomena occur around 400-500°C and exothermic phenomena dominate between 600 and 800°C.…”
Section: Effect Of Reaction Temperature On Chemical Reactionsmentioning
confidence: 99%
“…The shape and hierarchical pore structure also impact the heat and mass transfer properties of wood. Ciesielski et al 93 have shown, for example, that spherical representations of realistic biomass feedstocks fail to accurately capture the thermal gradients in a particle, though some effort has also been made to employ develop low-order mathematical approximations in spherical models to make them more accurate. 213 Pecha et al have further illustrated that the pore structure between even pine and poplar wood makes for differences in the external heat transfer coefficients.…”
Section: Secondary Reactionsmentioning
confidence: 99%
See 2 more Smart Citations